2001
DOI: 10.1016/s0378-1097(01)00093-3
|View full text |Cite
|
Sign up to set email alerts
|

Formation of allyl isothiocyanate from sinigrin in the digestive tract of rats monoassociated with a human colonic strain of Bacteroides thetaiotaomicron

Abstract: A human digestive strain of Bacteroides thetaiotaomicron was tested for its ability to metabolise sinigrin, a glucosinolate commonly found in Brassica vegetables. Gnotobiotic rats harbouring the bacterial strain were orally dosed with 50 Wmol sinigrin. HPLC analysis of the digestive contents showed that sinigrin was degraded in the large bowel, where B. thetaiotaomicron was established at a high level. Concurrently, a hydrolysis product of sinigrin, allyl isothiocyanate, was identified by GC-MS analysis, follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 19 publications
3
37
2
Order By: Relevance
“…Rat-diet supplemented with B. thetaiotaomicron 1 9 ND 100 (36 h) [19] Rat cecal microbiota 4 ND trace 100 (24 h) [20] Cecal [90] Human in vitro intestinal model 4 15 16 60 (24 h) [67] 5 * 19 20 (based on combined concentration of GSL 4 & 5) Rat intestinal microbiota 1 9 10 69 (6 h) [38] 1 9 (trace) 10 22…”
Section: Isothiocyanate Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rat-diet supplemented with B. thetaiotaomicron 1 9 ND 100 (36 h) [19] Rat cecal microbiota 4 ND trace 100 (24 h) [20] Cecal [90] Human in vitro intestinal model 4 15 16 60 (24 h) [67] 5 * 19 20 (based on combined concentration of GSL 4 & 5) Rat intestinal microbiota 1 9 10 69 (6 h) [38] 1 9 (trace) 10 22…”
Section: Isothiocyanate Productionmentioning
confidence: 99%
“…[18] This isolate was tested in gnotobiotic rats supplemented with sinigrin and it was found that allylisothiocyanate was produced in the digestive system, thus for the first time linking GSL metabolism with a specific bacterium. [19] Other workers have investigated rat cecal microbiota with a combination of glucoraphanin and bacterial growth media. [20] Here it was found that the rat cecal microbiota produced sulforaphane from GSL but only when supplemented with MRS (de Man, Rogosa, Sharpe), the media that supports the growth of Lactobacilli.…”
Section: Isothiocyanate Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very little work has been carried out on the degradative enzymes of the gut microflora, but more recently bacterial strains associated with glucosinolate degradation have been identified. The formation of allyl isothiocyanate (AITC) from 2-propenylglucosinolate in the digestive tract of rats monoassociated with a human colonic strain of Bacteroides thetaiotaomicron has been shown and it has been presumed that a bacterial myrosinase is involved [Elfoul et al, 2001]. The di-gestive fate of glucosinolates may be further influenced by the extent of cell rupture during ingestion, gastrointestinal transit time, meal composition, individual genotype and differences in colonic microflora.…”
Section: Isothiocyanatesmentioning
confidence: 99%
“…In damaged vegetable tissue containing released myrosinase, the glycosinolate sinigrin is converted to hydrolysis products in a manner that depends on the reaction conditions. In addition, myrosinase activity may be present in human colonic microflora, leading to the possibility that sinigrin is hydrolyzed in the gastrointestinal tract during digestion [50][51][52] . Fig.…”
Section: Allyl Nitrile Generation From Glucosinolate Sinigrinmentioning
confidence: 99%